THEORETICAL PRINCIPLES OF ASSESSING THE SOCIAL SECURITY OF THE REGION - Galyna Nazarova; Kateryna Demchenko (Сучасний стан наукових досліджень та технологій в промисловості, 2021)
The subject of research in the article is the theoretical foundations of the formation and development of the category of social security in the region. The purpose of the work is to analyze the preconditions for the formation of social security, to reveal the chronology of the formation of the concept of social security from the standpoint of international experience and to conduct an etymological, morphological analysis of the concept of social security. The article solves the following tasks: to investigate the theoretical aspects of the formation of the concept of social security, to determine the features and main directions of its development; to substantiate the expediency the approaches to social security; to conduct an etymological analysis of the concept of social security. The following methods are used: method of analysis and synthesis, classification-analytical method, abstract-logical method, historical-retrospective analysis and generalization. The following results were obtained: the definitions of foreign and Ukrainian scientists were systematized, morphological analysis was implemented, which made it possible to determine theoretical and methodological signs of this concept. The components of social security were justified: the macro level, the mesoroven and the micro level. The key ideas of the concept of social security, which are embedded in international and state normative legal acts, are identified. It has been proved that the reflection of the provisions of the concept of social security in international documents has influenced the practical implementation of developments in social policy around the world. The study of social security levels made it possible to distinguish the micro level, or personal level of human security. Based on the concept of social security, trends and results of social and economic processes are determined, while combining a system of goals, objectives, destabilizing and stabilizing factors of the external and internal environment. Conclusions: The analysis of social security has proved the need to focus the attention of the State on issues of social protection, namely interests, freedoms, preservation and development of human potential, ensuring a decent and high standard of living, regardless of age, gender, income level of the population. To assess the level and state of social security, it is proposed to use instrumental, situational, static, process, systemic and functional approaches. The concept of social security is complemented by modern studies of human capital, human development, and regional economy.